2004
DOI: 10.1007/s00125-003-1295-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a local angiotensin-generating system and dose-dependent inhibition of glucose-stimulated insulin release by angiotensin II in isolated pancreatic islets

Abstract: Aims/hypothesis. A local angiotensin-generating system has been found in the exocrine pancreas. This study aimed, primarily, to investigate the existence of a local angiotensin-generating system in the pancreatic islets and, secondly, to elucidate its role in regulating insulin secretion. Methods. Real-time RT-PCR and western blot were used to investigate if angiotensin-generating components are present in the mouse pancreatic islets, which are subject to regulation by islet transplantation. The localisation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
208
0
6

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 214 publications
(230 citation statements)
references
References 51 publications
16
208
0
6
Order By: Relevance
“…improvement has also recently been described in islets of the type 2 diabetic Zucker rat [27]. The improved first phase of glucose-stimulated insulin release in our experiments may be caused by direct effects of losartan on pancreatic beta cells, but this seems less likely in view of the fact that losartan, in our previous experiments in this strain [11], had no acute effects on glucose-stimulated insulin release, glucose oxidation or (pro)insulin biosynthesis in isolated islets. The latter finding was also confirmed for retrieved islet grafts in the present study.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…improvement has also recently been described in islets of the type 2 diabetic Zucker rat [27]. The improved first phase of glucose-stimulated insulin release in our experiments may be caused by direct effects of losartan on pancreatic beta cells, but this seems less likely in view of the fact that losartan, in our previous experiments in this strain [11], had no acute effects on glucose-stimulated insulin release, glucose oxidation or (pro)insulin biosynthesis in isolated islets. The latter finding was also confirmed for retrieved islet grafts in the present study.…”
Section: Discussionsupporting
confidence: 73%
“…In the present study, we found that the oxygenation and the first and second phases of glucosestimulated insulin release were decreased by angiotensin II in transplanted islets. Some of the effects of exogenously administered angiotensin II, especially on the second phase, may not just be related to vascular effects but may be direct negative effects on (pro)insulin biosynthesis, as recently reported [11].…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations